Prevalence and associated factors of psychological distress among caregivers of children with malnutrition: a cross‑sectional study - Biazin Yenealem Mekuriaw; Berhanie Getnet; Endris Seid; Tadese Teferi; Amare Alemwork; Mastewal Aschale; Aklile Tsega (BMC Public Health)
Abstract Background Malnutrition is a major child health problem in developing countries, contributing to 53% of child deaths annually. Psychological distress is an emotional and behavioral condition that causes significant suffering and interferes with a person’s daily life. Caregivers’ psychological distress can negatively impact a child’s development. Studies have shown that psychological distress has an impact on infant growth and nutritional status. However, evidence regarding the relationship between psychological distress and child malnutrition is scarce. Objectives The aim of this study was to determine the prevalence of psychological distress among caregivers of malnourished children and to identify factors associated with this. Methods This was a cross-sectional study was conducted and 409 caregivers participated. Outcome variable was assessed using Kessler Psychological Distress Scale (K-10).The collected data were analyzed using SPSS version 25. Bivariable and multivariable logistic analysis was conducted to identify factors associated with Psychological distress and Variables with P-value < 0.05 were considered to have significant association with 95% confidence interval. Results The prevalence Psychological distress among caregivers of malnourished children was 42.5%. Unemployment (AOR = 3.39, 95% CI: 2.14–9.11), poor socioeconomic status (AOR = 3.91, 95% CI: 1.46–9.34), low child feeding practices (AOR = 2.18, 95% CI: 1.12–4.21), poor social support (AOR = 4.44, 95% CI: 1.75–11.29), physical and emotional abuse (AOR = 3.37, 95% CI: 1.36–8.35), and child underweight (AOR = 4.36, 95% CI: 3.94–8.36) were factors statically significant associated with psychological distress. Conclusion Caregivers of malnourished children experienced high psychological distress linked to unemployment, poverty, poor feeding practices, poor social support, both physical and emotional abuse and child underweight. Therefore, strategies should focus on improving employment, strengthening social support, promoting proper child feeding, raising economic status, preventing abuse, and combating underweight to reduce caregiver psychological distress.